Predictors and efficacy of coping strategies among working parents. [article]. - Alampay, Regina Hechanova
The study surveyed 371 Filipino working parents in Metro Manila to determine the predictors and efficacy of their coping strategies. Educational attainment, age, gender, duality of income, and work level predicted the utilization of various coping strategies. Workers with low income and work levels, those in single-income families, and those who utilized passive coping strategies jobs reported most strain.